Dust control handbook - Mody, Vinit (Pollution technology review, 1988)
Consolidates information developed by industry and government laboratories on dust control engineering techniques. Designed for the minerals processing industry, the technology applies to other industries as well. Dust, its prevention, formation, and control are examined, including wet and dry control systems, personal protection, and testing methods.